STAR-RIS Empowered NOMA Systems With Caching and SWIPT - Thai-Hoc Vu; Anand Jee; Daniel Benevides da Costa; Sunghwan Kim (IEEE Open Journal of the Communications Society, 2024)
This paper proposes the joint use of caching and simultaneous wireless information and power transfer (SWIPT) to enhance the performance of cell-edge users of down-uplink simultaneously transmitting and reflecting reconfigurable intelligent surface (STAR-RIS)-empowered non-orthogonal multiple access (NOMA) systems. The main idea is to leverage the available caching at nearby users to establish cooperative communication while taking into account the problem of energy issues through SWIPT mechanisms, namely time-switching (TS) and power-splitting (PS) strategies. To improve the communication quality of users, STAR-RIS with an energy-splitting (ES) protocol is established and phase-shift design is formulated. Closed-form approximations and asymptotic expressions for users’ outage probability (OP) and effective ergodic capacity (EC) are derived. Based on the attained expressions, useful insights into system design, such as the impact of power allocation, imperfect successive interference cancellation, the number of transmit/reflect components on the system performance, trade-offs between the network requirement and the system performance, and trade-offs between the energy harvesting process and data transmission quality, are deduced. Numerical examples verify our derivations and show that: i) the performance of cell-edge users is improved significantly; ii) exploiting SWIPT-PS shows better OP and EC performance for nearby users compared to SWIPT-TS, while both provide comparable performance for cooperative communication; iii) as the performance of cell-edge users is mostly guaranteed, the communication quality of nearby users in downlink and source node in uplink can be improved by optimizing either the power budget or the energy harvesting factors; iv) adopting STAR-RIS with ES protocol outperforms mode-switching and time-splitting ones in terms of both OP and EC; and v) STAR-RIS-empowered NOMA has better EC performance than orthogonal-multiple access counterparts when SIC operation is properly designed.